Developing the EFL Teaching Process through Electronic Teaching- Portfolios Techniques. Case of: EFL Secondary Schools Teachers in Bejaia - MAOUCHE, Salima (Journal of Human Sciences, 2011)
This paper explores and examines the role the Electronic Teaching Portfolios play in developing the EFL teaching process in secondary schools in Bejaia. For this aim, important considerations have to be taken because we strongly believe that these tools if introduced and implemented by EFL teachers, they can not only serve as developmental and summative assessments for teachers, but they can also contribute in the conceptual experience in developing the teaching process as well. The general research questions directed in the present study are: (1) - How can web-based teaching portfolios bridge the gap between two parties typically not communicating with one another in order to promote the teaching practices? (2) – Do the web-based teaching portfolios prove to be effective tools with which to solicit participation of faculty and teaching staff towards progress